Default Risk on Islamic Banking in Indonesia - Budiandru Budiandru (Universitas Hayam Wuruk Perbanas, 2021)
The problem of default by debtors becomes a primary concern for Islamic banking recently. This study analyzes the effect of economic pressure on the risk of default on Islamic banks, both in the short and long term, the risk response of default, and also other variables' contribution in explaining the diversity of risk of default of Islamic banks. This study used monthly data from 2007 to 2020 by using a vector error correction model. The results show that inflation and exchange rates affect the risk of default in the short term, while inflation, exchange rates, and interest rates affect the risk of default in the long run. Non-performing financing quickly stabilized when responding to the interest rates. The Islamic stock index has the most significant contribution in explaining the diversity of default risks. Islamic banks must be aware of the monetary fluctuation and also careful in analyzing the demand for financing by looking at the future economic prospects.